Strengthening accountability: Lessons from inside and outside nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Accountability is the glue that connects commitment to action, and so strengthening it is a priority. Exercising accountability in nutrition is challenging because improving nutrition requires many different sectors to come together without an obvious institutional home. The six global nutrition targets for 2025 adopted by the World Health Assembly (WHA) are a key accountability mechanism, and we report on progress against them in Chapter 2. Here we identify and review other mechanisms—some from within nutrition, some outside—that can potentially be used to make nutrition actors more accountable to citizens, including those who are malnourished.